Comparative Analysis of Genetic Determinants Encoding Cadmium, Arsenic, and Benzalkonium Chloride Resistance in Listeria monocytogenes of Human, Food, and Environmental Origin - Gelbicova, Tereza; Florianova, Martina; Hluchanova, Lucie; Kalova, Alžběta; Korena, Kristýna; Strakova, Nicol; Karpiskova, Renáta (Frontiers in Microbiology, 2021)
Environmental adaptation of L. monocytogenes is a complex process involving various mechanisms that can contribute to their survival in the environment, further spread throughout the food chain and the development of listeriosis. The aim of this study was to analyze whole genome sequencing data in a set of 270 strains of L. monocytogenes derived from human listeriosis cases, food and environmental sources in order to compare the prevalence and type of genetic determinants encoding cadmium, arsenic and benzalkonium chloride resistance. Most of the detected genes of cadmium (27.8%), arsenic (15.6%) and benzalkonium chloride (7.0%) resistance was located on mobile genetic elements, even in phylogenetically distant lineages I and II, which indicates the possibility of their horizontal spread. While no differences were found in the prevalence of these genes between human and food strains, they have been detected sporadically in strains from the environment. Regarding cadmium resistance genes, cadA1C1_Tn5422 predominated, especially in clonal complexes (CC) 121, 8 and 3 strains. At the same time, qacH_Tn6188 encoding benzalkonium chloride resistance was most frequently detected in the genome of CC121 strains. Arsenic encoding resistance genes were detected mainly in strains CC2 (located on the chromosomal island LGI2) and CC9 (carried on Tn554). The results indicated a relationship between the spread of genes encoding resistance to cadmium, arsenic and benzalkonium chloride in certain serotypes and clonal complexes, and showed the need for a more extensive study of L. monocytogenes strains to better understand their ability to adapt to the food production environment.